Biaxial stretch can overcome discrepancy between global and local orientations of wavy collagen fibres - Turčanová, Michaela; Fischer, Jiří; Hermanová, Markéta; Bednařík, Zdeněk; Skácel, Pavel; Burša, Jiří (Journal of biomechanics, 2023)
Most frequently used structure-based constitutive models of arterial wall apply assumptions on two symmetric helical (and dispersed) fibre families which, however, are not well supported with histological findings where two collagen fibre families are seldom found. Moreover, bimodal distributions of fibre directions may originate also from their waviness combined with ignoring differences between local and global fibre orientations. In contrast, if the model parameters are identified without histological information on collagen fibre directions, the resulting mean angles of both fibre families are close to ±45°, which contradicts nearly all histologic findings. The presented study exploited automated polarized light microscopy for detection of collagen fibre directions in porcine aorta under different biaxial extensions and approximated the resulting histograms with unimodal and bimodal von Mises distributions. Their comparison showed dominantly circumferential orientation of collagen fibres. Their concentration parameter for unimodal distributions increased with circumferential load, no matter if acting uniaxially or equibiaxially. For bimodal distributions, the angle between both dominant fibre directions (chosen as measure of fibre alignment) decreased similarly for both uniaxial and equibiaxial loads. These results indicate the existence of a single family of wavy circumferential collagen fibres in all layers of the aortic wall. Bimodal distributions of fibre directions presented sometimes in literature may come rather from waviness of circumferentially arranged fibres than from two symmetric families of helical fibres. To obtain a final evidence, the fibre orientation should be analysed together with their waviness.
Keywords: kolagen; biomechanika; Concentration parameter; Fibre direction; Collagen; Aorta; arterie; Biomechanical Phenomena; aorta; Stress, Mechanical; Extracellular Matrix; Swine; zvířata; mechanický stres; prasata; Arterial wall; extracelulární matrix; Arteries; Fibre waviness; Animals